2018
DOI: 10.1002/fsn3.788
|View full text |Cite
|
Sign up to set email alerts
|

Improving nutritional status of children with Cerebral palsy: a qualitative study of caregiver experiences and community‐based training in Ghana

Abstract: BackgroundCerebral palsy (CP) is the most common childhood disability worldwide, and evidence shows that children with CP are at an increased risk of malnutrition due to feeding difficulties. This qualitative study explores caregiver experiences of feeding before and after a community‐based training program in Ghana.MethodsThirteen caregivers of children with CP, who were severely undernourished, were interviewed at the start of the training program. Eleven of these were interviewed again after a year of month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(60 citation statements)
references
References 20 publications
3
50
0
Order By: Relevance
“…In four studies the age range was partially overlapping with the focal ages for this review. In one study the age range of the children was 2 months to 9 years[ 37 ], in others it was 19–129 months[ 41 ], 1 year 5 months—11 years 11 months[ 42 ], and 18 months– 12 years[ 43 ]. In the last family caregiver study the age of the children was not specified[ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In four studies the age range was partially overlapping with the focal ages for this review. In one study the age range of the children was 2 months to 9 years[ 37 ], in others it was 19–129 months[ 41 ], 1 year 5 months—11 years 11 months[ 42 ], and 18 months– 12 years[ 43 ]. In the last family caregiver study the age of the children was not specified[ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Parents report the burden of feeding can be time-consuming and stressful for mothers. Typically, studies reported that the feeding of an infant with feeding difficulties was time consuming[ 38 40 , 42 , 43 , 44 ]. Parents reported experiencing frustration that they could not feed in the way they wanted to, such as breast-feeding[ 40 ], and that interventions and advice often did not ‘work’[ 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations